(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The paper theoretically substantiates the influence of defects in motor bearings on the form of their stator current and demonstrates the potential use of amplitude-defined spectral components of stator current as diagnostic indicators for bearing defects. It is shown that during bearing wear, rotor slot harmonics due to eccentricity directly interact with changes in magnetic conductivity across non-uniform air gaps, resulting in significant increases in harmonic amplitudes at rotor speed frequencies. Experimental investigations were conducted to validate these theoretical findings, confirming them comprehensively.